2018
DOI: 10.1177/1049732317747875
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Conceptualizations of Disease Among the Luo of Kenya

Abstract: The region inhabited by the Luo ethnic group in Kenya is disease endemic. However, disease awareness initiatives register low acceptance due to the sociocultural images of disease and illness conceptualized in the local Dholuo language in ways that may contradict modern biomedical knowledge and practice. This article evaluates the sociocultural basis of encoding descriptions of disease in the Luo indigenous knowledge system and their implications for modern medical practice. The methodology entailed use of qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Fang and Stewart (2018) found that the combined influences of health system factors, sociocultural factors, and traditional health and spiritual beliefs about hepatitis B affected the willingness of immigrant Hmong people (from the central valley region of northern California) to accept screenings and/or immunizations. Ojwang (2018) described the sociocultural conceptualizations of disease causation and experience as deeply embedded in the values, beliefs, and practices of the Luo people of Kenya, concluding that their ethnohistory informs their worldview. Rahemi’s (2019) and Rahemi, Dunphy, and Newman’s (2019) cross-sectional studies of older Iranians who immigrated to the United States during the first wave of immigrants in the 1950s revealed findings the researchers termed novel among contemporary elders.…”
Section: Culture Care Theory Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Fang and Stewart (2018) found that the combined influences of health system factors, sociocultural factors, and traditional health and spiritual beliefs about hepatitis B affected the willingness of immigrant Hmong people (from the central valley region of northern California) to accept screenings and/or immunizations. Ojwang (2018) described the sociocultural conceptualizations of disease causation and experience as deeply embedded in the values, beliefs, and practices of the Luo people of Kenya, concluding that their ethnohistory informs their worldview. Rahemi’s (2019) and Rahemi, Dunphy, and Newman’s (2019) cross-sectional studies of older Iranians who immigrated to the United States during the first wave of immigrants in the 1950s revealed findings the researchers termed novel among contemporary elders.…”
Section: Culture Care Theory Overviewmentioning
confidence: 99%
“…Wehbe-Alamah (2015) studied folk care beliefs of traditional Lebanese and Syrian Muslims in the Midwestern United States, discovering worldviews embedded in their Islamic religion and unique cultural beliefs and practices. From a study of the Luo tribe in Kenya, Ojwang (2018) discovered that their worldview was embedded in their common historical experience linking all tribal members to a single, common ancestor whom they held as the source of life. Their worldview as a community was encoded in generic linguistic expressions whose meanings were traditionally accessible only to insiders.…”
Section: Culture Care Theory Overviewmentioning
confidence: 99%
“…Dholuo is the native language of the Luo people. Dholuo is rich in its descriptions of illness and disease, some of which, not surprisingly, deviate from traditional Western biomedical concepts (Ojwang, 2018). We translated and adapted study instruments, two brief standard screeners for symptoms of depression and anxiety (see Measures), following World Health Organization (WHO) guidelines (World Health Organization, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Inevitably, problems with interpretation may arise. Difficulties in interpretation can arise from lack of familiarity with professional terminology, inability to interpret the cultural meaning of symptoms and behavior, and the inability to detect paralinguistic or nonverbal behavior (Hagan et al, 2013; Ojwang, 2018). The results can include, among others, the omission of information, poor paraphrasing, lack of translatable words or culturally equivalent concepts, inaccurate translation of words or concepts, and distortion of meaning leading to understatement or exaggeration (Tribe & Lane, 2009).…”
Section: Explaining Mental and Emotional Distress In The Shona Languagementioning
confidence: 99%
“…Others have observed that the presence of words that are either unknown, too scientific, or unusual to patients or participants create cultural distance between the clinician and patient (Bolton, 2002; Schlemmer & Mash, 2006). In mental health practice and research, everyday words, such as depression, health, or anxiety, need to be translated and understood in their cultural context as they may carry deeper meaning for a specific group (Ojwang, 2018; Sweetland, Belkin, & Verdeli, 2014; Ventevogel, Jordans, Reis, & de Jong, 2013).…”
Section: Explaining Mental and Emotional Distress In The Shona Languagementioning
confidence: 99%